Ray Tracing-Based Channel Modeling for Wireless Transmission in Indoor Environments - Izzat, Nabil Taufiq Nur; Hakim, Nurul Fahmi Arief; Kustiawan, Iwan; Arisesa, Hana; Al Qibtiya, Mariya; Ridwan, Azwar Mudzakkir (International Conference on Wireless and Telematics (Online), 2024)
The application of ray tracing techniques to channel modeling for MIMO-OFDM wireless communication systems in complex indoor environments will be the subject of this article. Signal propagation characteristics are analyzed using ray tracing methods, specifically the Shooting Bouncing Ray (SBR) method, which takes into account position variations between the transmitter (Tx) and receiver (Rx) and the impact of building materials on the channel. The research incorporates several parameters, namely received signal intensity, path loss, signal delay, and the number of interactions with the environment. A significant effect of Tx and Rx position changes on channel quality is demonstrated by the research findings. When the Rx is positioned at a greater distance from the Tx, path loss and signal delay increase. These results offer crucial insights for designers of wireless communications systems who are tasked with optimizing network performance while considering environmental factors that have an impact on signal propagation.